Réseau de suivi de la croissance de l'huître creuse en Bretagne. Synthèse des quatre années 1989 à 1992 - Littaye-mariette, Anne; Mazurie, Joseph (1993)
Since 1989, an homogeneous Crassostrea gigas oyster stock has been distributed once a year on several rearing sites in Brittany (3 populations per site). The main quantitative and qualitative growth descriptors, which reflect water quality effects during the monitoring period, are estimated at the end of each year. The 1989-1992 analysis prompted us to describe various growth responses correlated to biotops: oyster production in open areas influenced by oceanic waters was fairly constant in quality, including size and Polydora sp. infestation. In contrast, oysters in estuarine areas, partly affected by eutrophication (e.g., Aber Benoît, Pen Bé), or with a low carrying capacity, were characterized by weight and Polydora sp. infestation heterogeneity. These characteristics were almost constant over the years on all sites but Morlaix where oyster population growth tended to decrease. In 1993, the regional monitoring survey has been integrated into a national network called REMORA. Depuis 1989, des poches d'huîtres creuses de 18 mois, homogènes et de même provenance, sont disposées chaque année, au printemps, dans les principaux bassins ostréicoles bretons, à raison de 3 stations fixes par bassin. Les principaux descripteurs de la croissance et de la qualité des huîtres, estimés en fin d'année, sont ici synthétisés pour la période 1989-1992. Il se dessine une typologie opposant les bassins ouverts aux influences océaniques (Cancale, Paimpol) aux bassins plus enclavés : les premiers tendent à produire des huîtres de qualité moyenne et stable, tandis que les huîtres de rias ou d'estuaires montrent des performances plus irrégulières selon les sites et les années.